Changing patterns of research funding: threat or opportunity for research on forests. Discussion paper on Mobilising resources for forest research - Sayer, Jeffrey A.; Hunter, I. (1998)
A lower percentage of product value is invested in research in the forest sector than in many other sectors of the economy. Moreover, while it has been possible to reach a stable funding environment for research in some parts of the sector - notably in forest products - other aspects of forestry research are increasingly unattractive to funding agencies. The funding environment for forestry research is changing. Increasingly, state funding for commercial or proprietary research is being withdrawn in the expectation that such research will be taken up by the private sector. State funding is being applied to the issues that governments rate as important, either as a result of perceived public concern or as a result of international agreements. Competitive bidding is increasingly being used as a mechanism to allocate funds. This process has tended to favour small disciplinary teams doing component research at the expense of multi-disciplinary teams working at the systems level. In the Developed World the task is to improve the perceived value of forestry research; to adapt smoothly to the new research agenda created by changed demands placed upon forests and to maintain a balanced and progressive programme. In the Developing World the task is to build a research-capacity, an essential component of soundly-based, locally adapted development solutions, where often none exists. Given that state funding for many aspects of forestry research is not likely to increase and may decline, new sources of funding must be found. It is proposed that the role of Foundations, the GEF, Climate Change mitigation funds, the private sector and the commercial exploitation of research products be reviewed.